The Effect of Starting or Stopping Skin Cooling on the Thermoregulatory Responses During Leg Exercise in Humans - Demachi, K.; Yoshida, T.; Kume, M.; Tsuneoka, H. (International Journal of Sports Medicine, 2012)
To assess the effects of starting or stopping leg cooling on the thermoregulatory responses during exercise, 60 min of cycling exercise at 30% of maximal oxygen uptake was performed under 4 conditions using tube trouser perfused with water at 10°C; no leg cooling (NC), starting of leg cooling after 30 min of exercise (delayed cooling, DC), continuous leg cooling (CC), and stopping of continuous leg cooling after 30 min of exercise (SC) at an environmental temperature of 28.5°C. During exercise under the DC conditions, an instantaneous increase in the esophageal temperature (Tes), a suppression of the cutaneous vascular conductance at the forearm (%CVC), and a decrease in the mean skin temperature (Tsk) were observed after leg cooling. The total sweat loss (Δmsw,tot) was lower under the DC than the NC condition. In the SC study, however, the Tes remained constant, while the %CVC increased gradually after leg cooling was stopped, and the Δmsw,tot was greater than that under the CC condition. These results suggest that during exercise, rapid skin cooling of the leg may cause an increase in core temperature, while also enhancing thermal stress. However, stopping skin cooling did not significantly affect the core temperature long-term, because the skin blood flow and sweat rate subsequently increased.
Keywords: water-perfused trouser; body cooling; cutaneous vascular conductance; sweat loss